1995
DOI: 10.1182/blood.v85.4.1036.bloodjournal8541036
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated regulation of transferrin synthesis in mouse macrophages and human T lymphocytes

Abstract: Transferrin (Tf) plays an important role during immunologic activation by donating iron to activated lymphocytes. Therefore, synthesis by lymphomyeloid cells has been investigated. Mouse macrophages and macrophage cell lines synthesized Tf, with levels being markedly increased by gamma-interferon (gamma-IFN) and, to a lesser extent, by interleukin-1 beta (IL-1 beta), IL-6, and tumor necrosis factor alpha (TNF alpha). Tf was also produced by phytohemagglutinin-stimulated human T cells and two T-cell lines and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Transferrin is upregulated in microglia as well as astrocytes and oligodendrocytes following motor neuron injury (Tornquist et al, 1997). Cytokines, including TNF-␣, IL-1, and gamma interferon, induce transferrin in macrophages (Djeha et al, 1995), suggesting they might do the same in microglia and suggesting that transferrin might be an NF-B target gene.…”
Section: Transferrinmentioning
confidence: 99%
“…Transferrin is upregulated in microglia as well as astrocytes and oligodendrocytes following motor neuron injury (Tornquist et al, 1997). Cytokines, including TNF-␣, IL-1, and gamma interferon, induce transferrin in macrophages (Djeha et al, 1995), suggesting they might do the same in microglia and suggesting that transferrin might be an NF-B target gene.…”
Section: Transferrinmentioning
confidence: 99%
“…Several proteins highlighted in this study have been previously reported to have biomarker utility in LN or other renal diseases, primarily as markers of renal histology or for diagnostic purposes. ,,,,, For example, one study found urinary transferrin and ceruloplasmin to be increased 3 months prior to renal flare, and furthermore, transferrin only increased in patients that flared, making it an intriguing prognostic biomarker candidate . Transferrin is important for the regulation of iron homeostasis and levels of transferrin are thought to be altered by cytokines like interferon-γ that are known to play a role in LN disease pathogenesis . A separate study identified urinary afamin and ceruloplasmin as prognostic biomarkers in IgA nephropathy patients, a common cause of primary glomerulonephritis …”
Section: Discussionmentioning
confidence: 93%
“…18 Transferrin is important for the regulation of iron homeostasis and levels of transferrin are thought to be altered by cytokines like interferon-γ that are known to play a role in LN disease pathogenesis. 48 A separate study identified urinary afamin and ceruloplasmin as prognostic biomarkers in IgA nephropathy patients, a common cause of primary glomerulonephritis. 34 This study is the first to describe urinary vimentin as a potential biomarker in LN.…”
Section: ■ Discussionmentioning
confidence: 99%
“…В биологическом смысле ТФ является аутокринным активатором лимфоцитов. Синтез ТФ человеческими лимфоцитами происходит под влиянием цитокинов: гамма-интерферона (-ИФН), интерлейкина-1 (ИЛ-1), ИЛ-6, фактора некроза опухоли альфа (ФНО-), причем данные цитокины усиливают синтез ТФ в следующей убывающей последовательности: -ИФН > ИЛ-1 > ИЛ-6 > ФНО- [38]. Доказано, что избыточное количество ИЛ-2 в сыворотке крови больных с опухолями или хроническими воспалительными заболеваниями ингибирует синтез ферритина в макрофагах, но стимулирует синтез ТФ, что увеличивает содержание железа в крови, но не в тканях (тканевый дефицит железа) (Lissoni P. еt al., 1993).…”
Section: ии мечниковunclassified